A Chemically Recyclable Crosslinked Polymer Network Enabled by Orthogonal Dynamic Covalent Chemistry. (23rd August 2022) - Deng, Yuanxin; Zhang, Qi; Qu, Da‐Hui; Tian, He; Feringa, Ben L.
Abstract: Chemical recycling of synthetic polymers offers a solution for developing sustainable plastics and materials. Here we show that two types of dynamic covalent chemistry can be orthogonalized in a solvent‐free polymer network and thus enable a chemically recyclable crosslinked material. Using a simple acylhydrazine‐based 1, 2‐dithiolane as the starting material, the disulfide‐mediated reversible polymerization and acylhydrazone‐based dynamic covalent crosslinking can be combined in a one‐pot solvent‐free reaction, resulting in mechanically robust, tough, and processable crosslinked materials. The dynamic covalent bonds in both backbones and crosslinkers endow the network with depolymerization capability under mild conditions and, importantly, virgin‐quality monomers can be recovered and separated. This proof‐of‐concept study show opportunities to design chemically recyclable materials based on the dynamic chemistry toolbox. Abstract : Combining two types of dynamic covalent chemistries within a single network enables a chemically recyclable crosslinked material with excellent mechanical performances. Virgin‐quality monomers can be recovered and reused by efficient depolymerization under mild conditions.